2020
DOI: 10.2147/dmso.s237948
|View full text |Cite
|
Sign up to set email alerts
|

<p>Basal Insulin Initiation and Maintenance in Adults with Type 2 Diabetes Mellitus in the United States</p>

Abstract: Objective: A survey of US adults with type 2 diabetes mellitus was conducted to better understand patients' insulin initiation experiences and treatment persistence behaviors. Research Design and Methods: Participants were recruited from consumer panels and grouped by basal insulin treatment pattern: continuers (no gap of ≥7 days within 6 months of initiation); interrupters (gap ≥7 days, resumed treatment); discontinuers (stopped for ≥7 days, not resumed). A quota of approximately 50 respondents per persistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…36 Similarly, a more recent US survey reported that in 52.6% of individuals initiating basal insulin, potential weight gain was a major worry prior to commencement of therapy. 32 Such data suggest that medications with a no weight gain or potential weight loss profile could be preferred by people with T2D.…”
Section: Discussionmentioning
confidence: 99%
“…36 Similarly, a more recent US survey reported that in 52.6% of individuals initiating basal insulin, potential weight gain was a major worry prior to commencement of therapy. 32 Such data suggest that medications with a no weight gain or potential weight loss profile could be preferred by people with T2D.…”
Section: Discussionmentioning
confidence: 99%